The Development of Authentic Assessment Instruments on Drama Text Learning for Students of Class VIII in Junior High School 6 Tebing Tinggi - Yanti Gultom; Biner Ambarita; Syahnan Daulay (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to know the development of authentic assessment instruments on drama text learning for students of class VIII in Junior High School 6 Tebing Tinggi. This study used random sampling. The sample were 32 student and 3 teacher. The quality of authentic assessment instruments in drama text learning is obtained from the results of validation and assessment given by material experts, expert evaluations, teacher responses, and student responses. The result shows that the average value of the student's pretest was 68.56. Based on the average value of the student pretest data, it can be concluded that the ability of students does not experience a significant high increase and has not reached KKM. Learning by using authentic assessment instruments on drama text learning gained an average of 80.97. The lowest student score is 70 and the highest was 98. Based on the average value of student posttest data, it can be concluded that the ability of students to experience a significant increase was high and reaches KKM as expected. The effectiveness of the assessment instrument developed was 80.97% and the effectiveness before using the valuation instrument was 68.56%. Therefore, the level of students' ability to answer drama text questions increases after the product of authentic assessment instruments in drama text learning was applied in learning.